THE CONSUMPTION BEHAVIOR PATTERNS OF MUSLIM FAMILIES IN BUMI MADINA ASRI HOUSING SURABAYA ACCORDING TO THE MAQASHID SYARIAH PERSPECTIVE - Tanissa Intan Syahvina; Ririn Tri Ratnasari (Jurnal Ekonomi Syariah Teori dan Terapan, 2020)
The purpose of this research is to know the consumption behavior of the Muslim family from maqashid Syariah perspective to fulfill the needs of dharuriyyat, hajiyyat, and tahsiniyyat on religion, soul, intelligence, offspring, and wealth. The approach used in this research is qualitative with a descriptive strategy. In-depth interviews collected the data as primary data. This research focuses only on Muslim families who live in Bumi Madina Asri Housing in Surabaya to understand the consumption behavior of Muslim families from maqashid Syariah perspective. The result is all the Muslim families of Bumi Madina Asri Housing in Surabaya have fulfilled the needs of dharuriyyat, hajiyyat, and tahsiniyyat on maqashid Syariah aspect. However, some families still have not fulfilled the needs of hajiyyat and tahsiniyyat. Besides self-consumption, social consumption on the community of the Muslim family of Bumi Madina Asri Housing in Surabaya also has done very well. The payment of zakat, infaq and shodaqoh proves it. All the informants have given hibah, presents, and even some do waqf.Keywords: Muslim Family, Consumption Behavior, Muslim Consumer Behavior, Maqashid SyariahREFFERENCE Adiwarman A. Karim. (2008). Sejarah pemikiran ekonomi Islam. Jakarta: PT. Raja Grafindo.Al-Arif, M. Nur Rianto. (2011). Dasar-dasar ekonomi Islam. Solo: Era Adicitra Intermedia.Chalil, Zaki Fuad. (2009). Pemerataan distribusi kekayaan dalam ekonomi Islam. Yogyakarta: Penerbit ErlanggaDuhriah. (2015). Tingkatan-tingkatan maqashid al-syariah: al-dharruriyyat, al-hajiyyat dan al-tahsiniyyat. Jurnal, 1(1), 191-210. Fauzia, Ika Yunia dan Abdul Kadir Riyadi: (2014). Prinsip dasar ekonomi Islam perspektif maqashid al-syariah. Jakarta: Kencana.Hidayat, Muhammad. (2010). An introduction to the sharia economic. Jakarta: Zikrul Hakim.Khan, M. Fahim. (2014). Esai-esai Ekonomi Islam. Jakarta: PT Raja Grafindo.Kotler, Philip dan Kevin Lane Keller. (2016). Manajemen pemasaran, edisi ketiga belas. Jilid satu. Terjemahan oleh Bob Sabran. 2009. Jakarta: Penerbit Erlangga.Listiawati, (2012). Prinsip dasar ekonomi Islam. Palembang: Rafah Press.Masrur, Muhammad. (2017). Konsep harta dalam al-qur’an dan hadits. Jurnal Hukum Islam, 15(1), 96-105.Nafik, Muhammad. (2009). Bursa efek dan investasi syariah. Jakarta: Serambi Ilmu Semesta.Pusat Pengkajian dan Pengembangan Ekonomi Islam (P3EI). (2008). Ekonomi Islam. Jakarta: PT. Raja Grafindo.Rama, Ali dan Makhlani. (2013). Pembangunan ekonomi dalam tinjauan maqashid syariah. Fakultas Ekonomi dan Bisnis UIN Syarif Hidayatullah Jakarta dan Anggota Konsorsium Ekonomi Islam. Vol. 36, No.1, Agustus 2013.Rivai, Veithzal dkk. (2010). Islamic financial management. Bogor: Penerbit Ghalia Indonesia.Ryandono, Muhammad Nafik Hadi. (2010). Peran dan pengaruh penghimpunan dana terhadap penyaluran dana dan faktor kinerja bank serta kesejahteraan karyawan bank Islam di Indonesia. Disertasi tidak diterbitkan. Surabaya: Program Pascasarjana Universitas Airlangga.Sahliyah, Fatihatus. (2011). Kualitas sumber daya insani keluarga perspektif maqashid syariah. Skripsi tidak diterbitkan. Surabaya: Fakultas Ekonomi dan Bisnis Universitas Airlangga.Sugiyono. (2012). Metode penelitian kuantitatif, kualitatif dan R&D. Bandung: Alfabeta.Wibowo, Arif. (2012). Maqashid asy syariah: the ultimate objective of syariah. Islamic Finance Series. Yogyakarta: Universitas Negeri Yogyakarta.